A kind of polyurethane heat-conducting structural adhesive and preparation method thereof

By using raw materials such as modified castor oil and castor oil-modified polyester polyol, a polyurethane thermally conductive structural adhesive is prepared, which solves the problem of reduced bonding force and thermal conductivity caused by the high viscosity of the structural adhesive in the existing technology, and achieves high Bond strength, excellent flame retardant and thermal conductivity properties.

CN118064102BActive Publication Date: 2025-01-21HUIZHOU JUXIN CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410243705.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-04
Publication Date
2025-01-21
Estimated Expiration
2044-03-04

AI Technical Summary

Technical Problem

The existing two-component polyurethane thermally conductive structural adhesive has a large viscosity, resulting in incomplete contact with lithium batteries and degradation of adhesion and thermal conductivity.

Method used

Modified castor oil and castor oil-modified polyester polyol are used as basic raw materials, combined with coupling agents, modified thermally conductive flame retardant fillers and hydrophobic fumed silica, and through specific stirring and reaction conditions, component A is prepared and component B, and mix them in a specific mass ratio to form a polyurethane thermally conductive structural adhesive.

Benefits of technology

The bonding strength, flame retardant performance and thermal conductivity of the polyurethane thermally conductive structural adhesive are improved, ensuring close contact with lithium batteries and efficient heat conduction, and meeting the safety and performance requirements of power battery modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the technical field of polyurethane thermal conductive structural adhesive, and in particular to a polyurethane thermal conductive structural adhesive and a preparation method thereof. A polyurethane thermal conductive structural adhesive comprises component A and component B, wherein the component A comprises the following raw materials for preparation by mass: 12-15 parts of modified castor oil, 28-32 parts of castor oil modified polyester polyol, 1-2 parts of coupling agent, 40-55 parts of modified thermal conductive flame retardant filler, 2-4 parts of hydrophobic fumed silica; and the component B comprises the following raw materials for preparation by mass: 25-30 parts of isocyanate, 1-2 parts of coupling agent, 40-55 parts of modified thermal conductive flame retardant filler, 2-4 parts of hydrophobic fumed silica, and 0.5-1 parts of water remover. The polyurethane thermal conductive structural adhesive of the present application has high bonding strength, flame retardant performance and thermal conductivity, and has excellent aging resistance, which can meet the application requirements of power battery module structural adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of polyurethane thermal conductive structural adhesive, and in particular to a polyurethane thermal conductive structural adhesive and a preparation method thereof. Background Art

[0002] Lithium-ion batteries have the advantages of small size, high energy density, long cycle life, and low environmental pollution. Their applications in consumer electronics, new energy vehicles, energy storage devices, and other fields are gradually deepening, and the market demand is large and maintains rapid growth. With the rapid development of new energy vehicles, higher requirements are put forward for the structural adhesive used in lithium batteries. The structural adhesive must have good adhesion and thermal conductivity. In the prior art, due to the high viscosity of the structural adhesive, the structural adhesive is not in complete contact with the lithium battery, resulting in reduced adhesion and decreased thermal conductivity.

[0003] Therefore, the current two-component polyurethane thermal conductive structural adhesive still needs to be improved. Summary of the invention

[0004] The purpose of this application is to provide a polyurethane thermal conductive structural adhesive and a preparation method thereof in view of the deficiencies in the current technology.

[0005] In a first aspect, the present application provides a polyurethane thermal conductive structural adhesive, which adopts the following technical solution:

[0006] A polyurethane heat-conductive structural adhesive comprises a component A and a component B, wherein the mass ratio of the component A to the component B is 1-1.2:1; the component A comprises the following raw materials by mass: 12-15 parts of modified castor oil, 28-32 parts of castor oil-modified polyester polyol, 1-2 parts of a coupling agent, 40-55 parts of a modified heat-conductive flame-retardant filler, and 2-4 parts of hydrophobic fumed silica; the component B comprises the following raw materials by mass: 25-30 parts of isocyanate, 1-2 parts of a coupling agent, 40-55 parts of a modified heat-conductive flame-retardant filler, 2-4 parts of hydrophobic fumed silica, and 0.5-1 part of a water remover.

[0007] By adopting the above technical scheme, modified castor oil: as the basic raw material in polyurethane thermal conductive structural adhesive, it provides good bonding effect and strength. Castor oil modified polyester polyol: as the basic raw material in polyurethane thermal conductive structural adhesive, it has the advantages of low viscosity, aging resistance, high ignition point and good stability, which increases the flexibility and durability of the material and improves the bonding performance of the glue. Coupling agent: when preparing polyurethane thermal conductive structural adhesive, it plays a role in promoting reaction and improving the performance of glue, so that the glue has better bonding performance. Modified thermal conductive flame retardant filler: improves the flame retardant properties of polyurethane thermal conductive structural adhesive, and by dispersing in the continuous phase of polyurethane, a long and through heat transfer path is constructed, thereby improving the thermal conductivity. Hydrophobic gas-phase silica: improves the hydrophobicity of polyurethane thermal conductive structural adhesive, so that it can be in closer contact with the surface when coated on the battery surface, thereby improving the bonding effect. Isocyanate: As the basic raw material in polyurethane thermal conductive structural adhesive, it reacts with modified castor oil and castor oil modified polyester polyol in component A to form a polyurethane thermal conductive structure, improving the adhesive properties of the adhesive. Dehydrating agent: used to remove moisture from component B to avoid adverse effects on the glue reaction.

[0008] Preferably, the modified castor oil is composed of Ito H-368 modified castor oil, Vantellus T-400 modified castor oil and BASF Solvermol 805 modified castor oil in a mass ratio of 5-8:2-4:1.

[0009] Preferably, the method for preparing the castor oil-modified polyester polyol comprises the following steps:

[0010] S31. According to the mass fraction, 45-49 parts of castor oil and 10-12 parts of diethylene glycol are added to the reactor, mixed and stirred, and under the protection of nitrogen, 0.03-0.05 parts of tetrabutyl titanate are added, and the temperature is raised to 198°C, and the temperature is maintained for 2-3 hours to obtain product A; S32. According to the mass fraction, the temperature of product A is reduced to 133°C, and 2.5-3 parts of succinic acid are added under the protection of nitrogen, and the temperature is slowly increased to 195°C, and the temperature is maintained for 4-6 hours; after the reaction is completed, the product is cooled to room temperature to obtain product B;

[0011] S33. Add 0.1-0.2 parts of triethylamine to product B according to mass fractions, and react at room temperature for 20-30 minutes to obtain castor oil-modified polyester polyol.

[0012] By adopting the above technical scheme, in the preparation process of castor oil modified polyester polyol, castor oil reacts with diethylene glycol to form castor oil alcohol, then reacts with succinic acid to form castor oil modified polyester acid, and finally reacts with triethylamine to form castor oil modified polyester polyol. Castor oil modified polyester polyol has low viscosity, aging resistance, high ignition point and good stability, and has good adhesion to metal.

[0013] Preferably, the castor oil comprises the following preparation raw materials, measured by mass: 85 parts of ricinoleic acid, 5 parts of oleic acid, 5 parts of linoleic acid, 4 parts of palmitic acid and 1 part of stearic acid.

[0014] Preferably, the preparation method of the modified thermally conductive flame-retardant filler is as follows: by mass, 7.5 parts of isocyanate methyl trimethoxy silane are added to a mixture of 250 parts of cyclohexane and 100 parts of water and stirred evenly, and then 400 parts of boron nitride, 150 parts of flake graphite and 100 parts of magnesium hydroxide are added in sequence, stirred fully, heated to 73°C, refluxed for 60 minutes, the treated thermally conductive flame-retardant filler is filtered, dried, crushed, ground and sieved, and then plasma surface treated for 13 seconds under the conditions of a power of 3 kW and an oxygen volume concentration of 10% to obtain a modified thermally conductive flame-retardant filler.

[0015] Preferably, the boron nitride is composed of boron nitride with a particle size of 5-10 microns and boron nitride with a particle size of 20-30 microns in a mass ratio of 3:1; the particle size of the flake graphite is 20-40 microns; and the particle size of the magnesium hydroxide is 10-20 microns.

[0016] By adopting the above technical scheme, the compounding of different particles of boron nitride in the preparation method of modified thermal conductive flame retardant filler: by compounding different particles of boron nitride, the spatial network distribution of boron nitride in polyurethane thermal conductive structural adhesive can be improved, thereby improving the thermal conductivity effect. Magnesium hydroxide surface-modified by isocyanate methyl trimethoxysilane and plasma can improve the flame retardant properties of polyurethane thermal conductive structural adhesive, increase the flame suppression effect, and reduce the risk of flame propagation and combustion. Boron nitride and flake graphite surface-modified by isocyanate methyl trimethoxysilane and plasma improve the thermal conductivity of polyurethane thermal conductive structural adhesive through their synergistic effect, increase the heat transfer and dissipation efficiency, and improve the heat dissipation effect. The compounding of different particles of boron nitride and the surface-modified filler can construct a long and through heat transfer path in the glue, improving the thermal conductivity and flame retardant properties.

[0017] Preferably, the coupling agent is composed of isocyanate propyl triethoxy silane, isocyanate methyl trimethoxy silane and isocyanate methyl triethoxy silane in a mass ratio of 6:1-3:2.

[0018] By adopting the above technical scheme, isocyanate propyl triethoxysilane: one of the ingredients in the coupling agent can improve the compatibility of the components in the polyurethane thermal conductive structural adhesive, enhance the interaction between them, and promote the molding and curing process of the glue. Isocyanate methyl trimethoxy silane and isocyanate methyl triethoxy silane: other ingredients in the coupling agent can enhance the bonding performance in the polyurethane thermal conductive structural adhesive and improve the adhesion and durability of the glue. The combination of isocyanate propyl triethoxy silane, isocyanate methyl trimethoxy silane and isocyanate methyl triethoxy silane can achieve good compatibility and bonding performance, so that component A and component B can be evenly mixed to form a uniform polyurethane thermal conductive structural adhesive system. In summary, the role of the coupling agent in the polyurethane thermal conductive structural adhesive is to enhance the compatibility and bonding performance between the components and promote the molding and curing process of the glue. The synergistic effect of isocyanatepropyltriethoxysilane, isocyanatemethyltrimethoxysilane and isocyanatemethyltriethoxysilane can achieve better effects.

[0019] Preferably, the isocyanate is at least one of liquefied diphenylmethane diisocyanate, liquefied modified diphenylmethane-4,4'-diphenylmethane diisocyanate, and triphenylmethane triisocyanate.

[0020] Preferably, the dehydrating agent is composed of vinyltrimethoxysilane and 3A molecular sieve activated powder in a mass ratio of 1:12-15.

[0021] In a second aspect, the present application provides a method for preparing a polyurethane thermally conductive structural adhesive, using the following technical solution: As a general technical concept, the present application also provides a method for preparing the above-mentioned polyurethane thermally conductive structural adhesive, comprising the following steps:

[0022] S101, preparation of component A: first, according to the mass fractions, respectively add modified castor oil and castor oil-modified polyester polyol into a stirring kettle, set the speed to 300 rpm, control the temperature at 62°C, and stir for 10-15 min; then cool to 33°C, then add coupling agent, modified thermal conductive flame retardant filler and hydrophobic fumed silica in sequence, set the speed to 350 rpm, control the temperature to 48°C, maintain the vacuum degree at 0.05 MPa, stir for 40-60 min, cool to room temperature, and obtain component A;

[0023] S102, preparation of component B: first, add isocyanate into a stirring kettle according to the mass fraction, set the speed to 300 rpm, control the temperature at 40°C, and stir for 10-15 minutes; then add coupling agent, modified thermal conductive flame retardant filler, hydrophobic fumed silica and dewatering agent, set the speed to 350 rpm, control the temperature at 40°C, maintain the vacuum degree at 0.05 MPa, stir for 40-60 minutes, and cool to room temperature to obtain component B;

[0024] S103, mixing the prepared A and B components evenly at a mass ratio of 1-1.2:1 to obtain a polyurethane thermal conductive structural adhesive.

[0025] In summary, the beneficial technical effects of this application are:

[0026] 1. High bonding strength: Since castor oil-modified polyester polyol is used as one of the raw materials, it has good bonding properties and can ensure the firmness of the bonding part in the power battery module.

[0027] 2. Flame retardant performance: By introducing raw materials such as modified thermally conductive flame retardant fillers and isocyanate methyltrimethoxysilane, excellent flame retardant effect is achieved in the polyurethane thermal conductive structural adhesive, thus meeting the safety requirements of the battery module.

[0028] 3. Thermal conductivity: Hydrophobic fumed silica, magnesium hydroxide, boron nitride, flake graphite and other thermal conductive fillers are added to the polyurethane thermal conductive structural adhesive, which can form a long and continuous heat transfer path and improve the thermal conductivity of the glue.

[0029] 4. Aging resistance: Under environmental aging conditions, the bonding strength will not decay and has good stability, ensuring the long-term reliability of the bonded parts. DETAILED DESCRIPTION

[0030] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0031] Preparation Example 1 Preparation of castor oil modified polyester polyol

[0032] The preparation method of castor oil modified polyester polyol comprises the following steps:

[0033] S31, according to the mass fraction, 45kg of castor oil and 10kg of diethylene glycol are added into a reactor, mixed and stirred, and under the protection of nitrogen, 0.03kg of tetrabutyl titanate is added, and the temperature is raised to 198°C, and the temperature is maintained for reaction for 2h to obtain product A, wherein the castor oil comprises the following raw materials for preparation, according to the mass fraction: 85kg of ricinoleic acid, 5kg of oleic acid, 5kg of linoleic acid, 4kg of palmitic acid and 1kg of stearic acid;

[0034] S32, according to the mass fraction, cool the product A to 133°C, add 2.5 kg of succinic acid under nitrogen protection, slowly heat to 195°C, and keep the temperature for 4 hours; after the reaction, cool to room temperature to obtain product B;

[0035] S33. Add 0.1 kg of triethylamine to product B according to mass fractions, and react at room temperature for 20 minutes to obtain castor oil-modified polyester polyol.

[0036] Preparation Example 2 Preparation of castor oil modified polyester polyol

[0037] The preparation method of castor oil modified polyester polyol comprises the following steps:

[0038] S31, according to the mass fraction, 49kg castor oil and 12kg diethylene glycol were added into the reactor, mixed and stirred, and under the protection of nitrogen, 0.05kg tetrabutyl titanate was added, and the temperature was raised to 198°C, and the temperature was maintained for reaction for 3h to obtain product A, wherein the castor oil includes the following raw materials for preparation, according to the mass fraction: 85kg ricinoleic acid, 5kg oleic acid, 5kg linoleic acid, 4kg palmitic acid and 1kg stearic acid;

[0039] S32, according to the mass fraction, cool the product A to 133°C, add 3 kg of succinic acid under nitrogen protection, slowly heat to 195°C, and keep the temperature for reaction for 6 hours; after the reaction is completed, cool to room temperature to obtain product B;

[0040] S33. According to the mass fraction, 0.2 kg of triethylamine was added to the product B, and the mixture was reacted at room temperature for 30 min to obtain castor oil-modified polyester polyol.

[0041] Preparation Example 3 Preparation of castor oil modified polyester polyol

[0042] The preparation method of castor oil modified polyester polyol comprises the following steps:

[0043] S31, according to the mass fraction, 47kg castor oil and 11kg diethylene glycol were added into the reactor, mixed and stirred, and under the protection of nitrogen, 0.04kg tetrabutyl titanate was added, and the temperature was raised to 198°C, and the temperature was maintained for reaction for 2.5h to obtain product A, wherein the castor oil includes the following raw materials for preparation, according to the mass fraction: 85kg ricinoleic acid, 5kg oleic acid, 5kg linoleic acid, 4kg palmitic acid and 1kg stearic acid;

[0044] S32, according to the mass fraction, cool the product A to 133°C, add 2.8 kg of succinic acid under nitrogen protection, slowly raise the temperature to 195°C, and keep the temperature for reaction for 5 hours; after the reaction is completed, cool to room temperature to obtain product B;

[0045] S33. According to the mass fraction, 0.15 kg of triethylamine was added to the product B, and the mixture was reacted at room temperature for 25 min to obtain castor oil-modified polyester polyol.

[0046] Preparation Example 4 Preparation of modified thermally conductive flame retardant filler

[0047] The preparation method of the modified thermally conductive flame-retardant filler is as follows: according to the mass fraction, 7.5 kg of isocyanate methyl trimethoxy silane is added to a mixture of 250 kg of cyclohexane and 100 kg of water and stirred evenly, and then 400 kg of boron nitride, 150 kg of flake graphite and 100 kg of magnesium hydroxide are added in sequence, stirred fully, heated to 73°C, and refluxed for 60 minutes. The treated thermally conductive flame-retardant filler is filtered, dried, crushed, ground, and sieved, and then plasma surface treated for 13 seconds under the conditions of a power of 3 kW and an oxygen volume concentration of 10%, to obtain the modified thermally conductive flame-retardant filler, wherein the boron nitride is composed of boron nitride with a particle size of 5-10 microns and boron nitride with a particle size of 20-30 microns in a mass fraction ratio of 3:1; the particle size of the flake graphite is 20-40 microns; and the particle size of the magnesium hydroxide is 10-20 microns.

[0048] Example 1

[0049] A polyurethane heat-conducting structural adhesive comprises a component A and a component B, wherein the mass ratio of the component A to the component B is 1:1; the component A comprises the following raw materials by mass: 12 kg of modified castor oil, 28 kg of castor oil-modified polyester polyol, 1 kg of coupling agent, 40 kg of modified heat-conducting flame-retardant filler, and 2 kg of hydrophobic fumed silica; the component B comprises the following raw materials by mass: 25 kg of liquefied diphenylmethane diisocyanate, 1 kg of coupling agent, 40 kg of modified heat-conducting flame-retardant filler, 2 kg of hydrophobic fumed silica, and 0.5 kg of water remover, wherein the modified castor oil is prepared by Ito H- 368 modified castor oil, Vantellus T-400 modified castor oil and BASF Solvermol805 modified castor oil are composed of a mass ratio of 5:2:1, the coupling agent is composed of isocyanate propyl triethoxysilane, isocyanate methyl trimethoxysilane and isocyanate methyl triethoxysilane in a mass ratio of 6:1:2, the dehydrating agent is composed of vinyl trimethoxysilane and 3A molecular sieve activated powder in a mass ratio of 1:12, the modified thermally conductive flame retardant filler is the modified thermally conductive flame retardant filler prepared in Preparation Example 4; the castor oil modified polyester polyol is the castor oil modified polyester polyol prepared in Preparation Example 1.

[0050] The method for preparing the above-mentioned polyurethane thermal conductive structural adhesive comprises the following steps:

[0051] S101, preparation of component A: first, according to the mass fractions, respectively add modified castor oil and castor oil-modified polyester polyol into a stirring kettle, set the speed to 300 rpm, control the temperature at 62°C, and stir for 10 min; then cool to 33°C, then add coupling agent, modified thermal conductive flame retardant filler and hydrophobic fumed silica in sequence, set the speed to 350 rpm, control the temperature to 48°C, maintain the vacuum degree at 0.05 MPa, stir for 40 min, cool to room temperature, and obtain component A;

[0052] S102, preparation of component B: first, according to the mass fraction, add liquefied diphenylmethane diisocyanate into a stirring kettle, set the speed to 300 rpm, control the temperature at 40°C, and stir for 10 minutes; then add a coupling agent, a modified thermally conductive flame-retardant filler, a hydrophobic fumed silica and a water scavenger, set the speed to 350 rpm, control the temperature at 40°C, maintain the vacuum degree at 0.05 MPa, stir for 40 minutes, and cool to room temperature to obtain component B;

[0053] S103, mixing the prepared A and B components in a mass ratio of 1:1 to obtain a polyurethane thermal conductive structural adhesive.

[0054] Example 2

[0055] A polyurethane heat-conducting structural adhesive comprises a component A and a component B, wherein the mass ratio of the component A to the component B is 1.2:1; the component A comprises the following raw materials by mass: 15 kg of modified castor oil, 32 kg of castor oil-modified polyester polyol, 2 kg of coupling agent, 55 kg of modified heat-conducting flame-retardant filler, and 4 kg of hydrophobic fumed silica; the component B comprises the following raw materials by mass: 30 kg of liquefied modified diphenylmethane-4,4'-diphenylmethane diisocyanate, 2 kg of coupling agent, 55 kg of modified heat-conducting flame-retardant filler, 4 kg of hydrophobic fumed silica, and 1 kg of dehydrating agent; The sesame oil is composed of Ito H-368 modified castor oil, Vantellus T-400 modified castor oil and BASF Solvermol805 modified castor oil in a mass ratio of 8:4:1, the coupling agent is composed of isocyanate propyl triethoxysilane, isocyanate methyl trimethoxysilane and isocyanate methyl triethoxysilane in a mass ratio of 6:3:2, the dehydrating agent is composed of vinyl trimethoxysilane and 3A molecular sieve activation powder in a mass ratio of 1:15, the modified thermal conductive flame retardant filler is the modified thermal conductive flame retardant filler prepared in Preparation Example 4; the castor oil modified polyester polyol is the castor oil modified polyester polyol prepared in Preparation Example 2.

[0056] The method for preparing the above-mentioned polyurethane thermal conductive structural adhesive comprises the following steps:

[0057] S101, preparation of component A: first, according to the mass fractions, respectively add modified castor oil and castor oil-modified polyester polyol into a stirring kettle, set the speed to 300 rpm, control the temperature at 62°C, and stir for 15 minutes; then cool to 33°C, then add coupling agent, modified thermal conductive flame retardant filler and hydrophobic fumed silica in sequence, set the speed to 350 rpm, control the temperature to 48°C, maintain the vacuum degree at 0.05 MPa, stir for 60 minutes, cool to room temperature, and obtain component A;

[0058] S102, preparation of component B: first, according to the mass fraction, add liquefied modified diphenylmethane-4,4'-diphenylmethane diisocyanate into a stirring kettle, set the speed to 300 rpm, control the temperature at 40°C, and stir for 15 minutes; then add a coupling agent, a modified thermally conductive flame-retardant filler, a hydrophobic fumed silica and a water scavenger, set the speed to 350 rpm, control the temperature at 40°C, maintain the vacuum degree at 0.05 MPa, stir for 60 minutes, and cool to room temperature to obtain component B;

[0059] S103, mixing the prepared A and B components in a mass ratio of 1.2:1 to obtain a polyurethane thermal conductive structural adhesive.

[0060] Example 3

[0061] A polyurethane heat-conducting structural adhesive comprises a component A and a component B, wherein the mass ratio of the component A to the component B is 1.1:1; the component A comprises the following raw materials by mass: 14 kg of modified castor oil, 30 kg of castor oil-modified polyester polyol, 1.5 kg of coupling agent, 48 kg of modified heat-conducting flame-retardant filler, and 3 kg of hydrophobic fumed silica; the component B comprises the following raw materials by mass: 28 kg of triphenylmethane triisocyanate, 1.5 kg of coupling agent, 48 kg of modified heat-conducting flame-retardant filler, 3 kg of hydrophobic fumed silica, and 0.8 kg of water remover, wherein the modified castor oil is prepared by Ito H-368 modified castor oil, Vantellus T-400 modified castor oil and BASF Solvermol805 modified castor oil are composed of a mass ratio of 7:3:1, the coupling agent is composed of isocyanate propyl triethoxysilane, isocyanate methyl trimethoxysilane and isocyanate methyl triethoxysilane in a mass ratio of 3:1:1, the dehydrating agent is composed of vinyl trimethoxysilane and 3A molecular sieve activated powder in a mass ratio of 1:13, the modified thermally conductive flame retardant filler is the modified thermally conductive flame retardant filler prepared in Preparation Example 4; the castor oil modified polyester polyol is the castor oil modified polyester polyol prepared in Preparation Example 3.

[0062] The method for preparing the above-mentioned polyurethane thermal conductive structural adhesive comprises the following steps:

[0063] S101, preparation of component A: first, according to the mass fractions, respectively add modified castor oil and castor oil-modified polyester polyol into a stirring kettle, set the speed to 300 rpm, control the temperature at 62°C, and stir for 13 minutes; then cool to 33°C, then add coupling agent, modified thermal conductive flame retardant filler and hydrophobic fumed silica in sequence, set the speed to 350 rpm, control the temperature to 48°C, maintain the vacuum degree at 0.05 MPa, stir for 50 minutes, cool to room temperature, and obtain component A;

[0064] S102, preparation of component B: first, triphenylmethane triisocyanate is added to a stirring kettle according to the mass fraction, the speed is set to 300 rpm, the temperature is controlled at 40°C, and stirring is performed for 13 minutes; then, a coupling agent, a modified thermally conductive flame-retardant filler, a hydrophobic fumed silica and a water scavenger are added, the speed is set to 350 rpm, the temperature is controlled at 40°C, the vacuum degree is maintained at 0.05 MPa, stirring is performed for 50 minutes, and cooling is performed to room temperature to obtain component B;

[0065] S103, mixing the prepared A and B components in a mass ratio of 1.1:1 to obtain a polyurethane thermal conductive structural adhesive.

[0066] Example 4

[0067] The same as Example 3, except that an equal amount of isocyanate propyl triethoxy silane is used instead of the coupling agent, and the coupling agent is composed of isocyanate propyl triethoxy silane, isocyanate methyl trimethoxy silane and isocyanate methyl triethoxy silane in a mass ratio of 3:1:1.

[0068] Example 5

[0069] The same as Example 3, except that an equal amount of isocyanate methyl trimethoxy silane is used instead of the coupling agent, and the coupling agent is composed of isocyanate propyl triethoxy silane, isocyanate methyl trimethoxy silane and isocyanate methyl triethoxy silane in a mass ratio of 3:1:1.

[0070] Example 6

[0071] The same as Example 3, except that an equal amount of isocyanate methyl triethoxy silane is used instead of the coupling agent, and the coupling agent is composed of isocyanate propyl triethoxy silane, isocyanate methyl trimethoxy silane and isocyanate methyl triethoxy silane in a mass ratio of 3:1:1.

[0072] Comparative Example 1

[0073] The same as Example 3, except that an equal amount of modified castor oil polyol AC009 produced by Ito Corporation of Japan is used to replace the castor oil modified polyester polyol prepared in Preparation Example 3 of the present application.

[0074] Comparative Example 2

[0075] The same as Example 3, except that an equal amount of filler prepared by mixing 400 kg of boron nitride with a particle size of 5-10 microns, 150 kg of flake graphite and 100 kg of magnesium hydroxide (the particle size of the flake graphite is 20-40 microns, and the particle size of the magnesium hydroxide is 10-20 microns) is used instead of the modified thermally conductive flame retardant filler prepared in Preparation Example 4 of the present application.

[0076] Comparative Example 3

[0077] The same as Example 3, except that an equal amount of filler prepared by mixing 400 kg of boron nitride with a particle size of 20-30 microns, 150 kg of flake graphite and 100 kg of magnesium hydroxide (the particle size of the flake graphite is 20-40 microns, and the particle size of the magnesium hydroxide is 10-20 microns) is used instead of the modified thermally conductive flame retardant filler prepared in Preparation Example 4 of the present application.

[0078] Comparative Example 4

[0079] The same as Example 3, except that an equal amount of filler prepared by mixing 550 kg of boron nitride and 100 kg of magnesium hydroxide (the boron nitride consists of boron nitride with a particle size of 5-10 microns and boron nitride with a particle size of 20-30 microns in a mass ratio of 3:1; the particle size of the magnesium hydroxide is 10-20 microns) is used instead of the modified thermally conductive flame retardant filler prepared in Preparation Example 4 of this application.

[0080] Comparative Example 5

[0081] The same as Example 3, except that an equal amount of filler prepared by mixing 550 kg of flake graphite and 100 kg of magnesium hydroxide (the particle size of the flake graphite is 20-40 microns, and the particle size of the magnesium hydroxide is 10-20 microns) is used instead of the modified thermally conductive flame retardant filler prepared in Preparation Example 4 of the present application.

[0082] Performance Testing

[0083] The polyurethane thermally conductive structural adhesive prepared in Example 1, Example 6 and Comparative Examples 1 to Comparative Examples 5 was coated on the surface of a polytetrafluoroethylene plate. After aging at 25° C. for 7 days, a polyurethane thermally conductive structural adhesive layer with a thickness of 200 μm was formed. The Shore hardness and thermal conductivity of the polyurethane thermally conductive structural adhesive were measured. The thermal conductivity was tested according to the ASTM D-5470 test method, and the Shore hardness was tested according to the GB / T 2411-1980 standard. The results are shown in Table 1.

[0084] The polyurethane thermal conductive structural adhesive prepared in Examples 1 to 6 and Comparative Examples 1 to 5 was used for bonding 3 series aluminum sheets (aluminum-manganese alloy aluminum sheets, 2 mm thick). After aging at 25° C. for 7 days, the thickness of the polyurethane thermal conductive structural adhesive layer was 200 μm. Referring to the national standard GB7124, the shear strength of the polyurethane thermal conductive structure was measured, denoted as S0. The results are shown in Table 1.

[0085] The polyurethane thermally conductive structural adhesive prepared in Examples 1 to 6 and Comparative Examples 1 to 5 was used to bond 3 series aluminum sheets (upper layer), PET (middle layer), and 3 series aluminum sheets (lower layer) to obtain a "sandwich" structure. After aging at 25°C for 7 days, the thickness of the polyurethane thermally conductive structural adhesive layer was 200 μm. Referring to the national standard GB7124, the shear strength of the polyurethane thermally conductive structural adhesive was measured, recorded as S1. The results are shown in Table 1.

[0086] Aging resistance: The polyurethane thermally conductive structural adhesive prepared in Examples 1 to 6 and Comparative Examples 1 to 5 was used for bonding between 3 series aluminum sheets (upper layer), PET (middle layer), and 3 series aluminum sheets (lower layer) (i.e., sandwich structure). The thickness of the polyurethane thermally conductive structural adhesive layer formed after curing was 200 μm. The entire polyurethane thermally conductive structural adhesive was placed under 85°C and 85% RH conditions for 1000 h, and the shear strength of the polyurethane thermally conductive structural adhesive was measured with reference to the national standard GB7124, denoted as S2. The shear strength attenuation rate was calculated by the formula R1 = (S1-S2) × 100% / S1. The results are shown in Table 1.

[0087] The polyurethane thermally conductive structural adhesive prepared in Examples 1 to 6 and Comparative Examples 1 to 5 was used for bonding between 3 series aluminum sheets (upper layer), PET (middle layer), and 3 series aluminum sheets (lower layer) (i.e., sandwich structure). After aging at 25°C for 7 days, the thickness of the polyurethane thermally conductive structural adhesive layer was 200 μm. The entire polyurethane thermally conductive structural adhesive was subjected to a thermal shock test (-45 to 85°C, 500 cycles, 1000 h). Referring to the national standard GB7124, the shear strength of the polyurethane thermally conductive structural adhesive was measured, denoted as S3, and the shear strength attenuation rate was calculated by the formula R2 = (S1-S3) / S1×100%. The results are shown in Table 1.

[0088] Flame retardant grade: The flame retardant grade was determined according to GB 8410-2006 “Combustion characteristics of automotive interior materials”. The results are shown in Table 1.

[0089] Table 1 Performance test

[0090]

[0091]

[0092] As can be seen from Table 1, the polyurethane thermal conductive structural adhesives prepared in Examples 1 to 3 have good thermal conductivity, thermal conductivity ≥ 2.3W / (m·K), flame retardant grade UL94 is V-0, Shore hardness is between 60-64D, shear strength S0 is between 13.5-14.1MPa, shear strength S1 is between 12.3-12.7MPa; shear strength attenuation rate R1 is between 0.5-3.3%, and shear strength attenuation rate R1 is between 1.4-7.1%. The polyurethane thermal conductive structural adhesive of the present application has high bonding strength, flame retardant properties and thermal conductivity, and has excellent aging resistance, which can meet the application requirements of power battery module structural adhesives.

[0093] As can be seen from Table 1, the performance comparison analysis of the polyurethane thermal conductive structural adhesives prepared in Example 3 and Example 4-Example 6 shows that the coupling agent is composed of isocyanate propyl triethoxy silane, isocyanate methyl trimethoxy silane and isocyanate methyl triethoxy silane in a mass ratio of 3:1:1. The synergistic effect between them can improve the comprehensive performance of the polyurethane thermal conductive structural adhesive.

[0094] As can be seen from Table 1, the comparative analysis of the performance of the polyurethane thermal conductive structural adhesive prepared in Example 3 and Comparative Example 1 shows that the castor oil-modified polyester polyol prepared in Preparation Example 3 is effective in improving the bonding strength of the polyurethane thermal conductive structural adhesive.

[0095] As can be seen from Table 1, the performance comparison analysis of the polyurethane thermally conductive structural adhesive prepared in Example 3 and Comparative Examples 2-3 shows that the boron nitride is composed of boron nitride with a particle size of 5-10 microns and boron nitride with a particle size of 20-30 microns in a mass ratio of 3:1. By compounding boron nitride with different particle sizes, the spatial network distribution of boron nitride in the polyurethane thermally conductive structural adhesive is improved, thereby improving the thermal conductivity of the polyurethane thermally conductive structural adhesive.

[0096] As can be seen from Table 1, the performance comparison analysis of the polyurethane thermally conductive structural adhesives prepared in Example 3 and Comparative Examples 4-5 shows that the compounding of boron nitride and flake graphite and the synergistic effect therebetween are used to improve the spatial network distribution of the modified thermally conductive flame retardant filler in the polyurethane thermally conductive structural adhesive, thereby improving the thermal conductivity of the polyurethane thermally conductive structural adhesive.

[0097] The above embodiments are only used to explain the technical solutions of the present application rather than to limit them. Although the above embodiments provide a specific description of the present application, relevant technical personnel should understand that the specific implementation modes of the present invention can still be modified or replaced by equivalents, and any modifications and equivalent replacements that do not depart from the spirit and scope of the present application should be included in the scope of protection of the present application.

Claims

1. A polyurethane thermal conductive structural adhesive, characterized in that: The invention comprises component A and component B, wherein the mass ratio of component A to component B is 1-1.2:1; the component A comprises the following raw materials by mass: 12-15 parts of modified castor oil, 28-32 parts of castor oil-modified polyester polyol, 1-2 parts of coupling agent, 40-55 parts of modified thermal conductive flame retardant filler, and 2-4 parts of hydrophobic fumed silica; The B component includes the following raw materials by weight: 25-30 parts of isocyanate, 1-2 parts of coupling agent, 40-55 parts of modified thermal conductive flame retardant filler, 2-4 parts of hydrophobic fumed silica, and 0.5-1 parts of dehydrating agent; The modified castor oil is composed of Ito H-368 modified castor oil, Vantellus T-400 modified castor oil and BASF Solvermol 805 modified castor oil in a mass ratio of 5-8:2-4:1; The preparation method of the castor oil modified polyester polyol comprises the following steps: S31, according to the mass parts, add 45-49 parts of castor oil and 10-12 parts of diethylene glycol into a reactor, mix and stir, under nitrogen protection, add 0.03-0.05 parts of tetrabutyl titanate, heat to 198 ° C, keep the temperature for 2-3 hours, and obtain product A, wherein the castor oil comprises the following preparation raw materials: 85 parts of ricinoleic acid, 5 parts of oleic acid, 5 parts of linoleic acid, 4 parts of palmitic acid and 1 part of stearic acid; S32, according to the mass fraction, cool the product A to 133°C, add 2.5-3 parts of succinic acid under nitrogen protection, slowly heat to 195°C, maintain the temperature for 4-6 hours; after the reaction is completed, cool to room temperature to obtain product B; S33, adding 0.1-0.2 parts of triethylamine to product B according to mass fractions, reacting at room temperature for 20-30 minutes to obtain castor oil-modified polyester polyol; The preparation method of the modified thermal conductive flame retardant filler is as follows: by weight, 7.5 parts of isocyanate methyl trimethoxy silane are added to a mixture of 250 parts of cyclohexane and 100 parts of water, and the mixture is stirred evenly; then 400 parts of boron nitride, 150 parts of flake graphite and 100 parts of magnesium hydroxide are added in sequence, the mixture is stirred fully, heated to 73° C., and refluxed for 60 minutes; the treated thermal conductive flame retardant filler is filtered, dried, crushed, ground, and sieved; and then plasma surface treated for 13 seconds under the conditions of a power of 3 kW and an oxygen volume concentration of 10% to obtain the modified thermal conductive flame retardant filler, wherein the boron nitride is composed of boron nitride with a particle size of 5-10 microns and boron nitride with a particle size of 20-30 microns in a mass ratio of 3:1; the particle size of the flake graphite is 20-40 microns; and the particle size of the magnesium hydroxide is 10-20 microns; The coupling agent is composed of isocyanate propyl triethoxysilane, isocyanate methyl trimethoxysilane and isocyanate methyl triethoxysilane in a mass ratio of 6:1-3:

2.

2. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The isocyanate is at least one of liquefied diphenylmethane diisocyanate, liquefied modified diphenylmethane-4,4'-diphenylmethane diisocyanate, and triphenylmethane triisocyanate.

3. The polyurethane thermal conductive structural adhesive according to claim 1, characterized in that: The dehydrating agent is composed of vinyl trimethoxysilane and 3A molecular sieve activation powder in a mass ratio of 1:12-15.

4. A method for preparing a polyurethane thermal conductive structural adhesive according to any one of claims 1 to 3, characterized in that: The following steps are involved: S101, preparation of component A: first, according to the mass fractions, respectively add modified castor oil and castor oil-modified polyester polyol into a stirring kettle, set the speed to 300 rpm, control the temperature at 62°C, and stir for 10-15 min; then cool to 33°C, then add coupling agent, modified thermal conductive flame retardant filler and hydrophobic fumed silica in sequence, set the speed to 350 rpm, control the temperature to 48°C, maintain the vacuum degree at 0.05 MPa, stir for 40-60 min, cool to room temperature, and obtain component A; S102, preparation of component B: first, add isocyanate into a stirring kettle according to the mass fraction, set the speed to 300 rpm, control the temperature at 40°C, and stir for 10-15 minutes; then add coupling agent, modified thermal conductive flame retardant filler, hydrophobic fumed silica and dewatering agent, set the speed to 350 rpm, control the temperature at 40°C, maintain the vacuum degree at 0.05 MPa, stir for 40-60 minutes, and cool to room temperature to obtain component B; S103, mixing the prepared A and B components evenly at a mass ratio of 1-1.2:1 to obtain a polyurethane thermal conductive structural adhesive.

Citation Information

Patent Citations

  • Two-component polyurethane structural adhesive and preparation method thereof

    CN112608707A

  • High-thermal-conductivity two-component polyurethane structure adhesive as well as preparation method and application thereof

    CN114133910A